Detection of porcine adulteration in cosmetic cream formulation via TaqMan probe real-time polymerase chain reaction - Mustafa, Suhana (2020)
Halal authentication in the cosmetic cream is relatively a new study. Biomolecular approach is said to be efficient and effective for the detection of species-specific target. However, the complex matrices that came from the variety composition of the ingredients and the harsh process have become challenges for the detection of species specific targeting porcine. This challenges are due to the fragmentation of high molecular weight DNA (Deoxyribonucleic acid) into a smaller fragment and high possibility of denaturation of DNA. The challenges in detection become more significance as there are ingredients that are potentially can inhibit the Polymerase Chain Reaction (PCR) to be happened. Ethylenediaminetetraacetic acid (EDTA) is one the common ingredients that are used in the cosmetic cream are found can inhibit the PCR reaction due to its chelates properties. This aim of this research is to study the on the Halal detection targeting porcine as the species-specific in cosmetic cream using real time PCR (qPCR) as a detection tool. Hence, the laboratory prepared cream was formulated with the addition of the 10% (w/w) EDTA. A part from that, lard was spiked into the prepared cream ranging from 1%, 3% and 5% (w/w). A modified Cetyl trimethylammonium bromide (CTAB) method was developed that encompassed on pre-treatment sample and purification method and successfully extracted the DNA. These qPCR assays were subjected to the 1%, 3% and 5% of lard containing cream samples providing their Cq value respectively. Universal primer 18s rRNA TaqMan qPCR was employed. This assay had amplified all the samples at 187 bp at the Cq value of 33.490.08, 32.310.11 and 23.490.17 contributing that eukaryotic DNA was successfully extracted from the prepared cream. Hence further analysis employing TaqMan qPCR was done with the porcine-specific primer involving MPRE (nuclear DNA) and Cyt b gene (mitochondrial DNA). These two primers were utilized as a sensitivity comparison study between the nuclear DNA and mitochondrial DNA. Cyt b had successfully amplified the samples at 109 bp at the Cq value of 35.890.55, 36.780.38 and 24.140.19 while there was negative amplification of the MPRE. The porcine commercial cream branding ROREC that contained porcine derivatives was tested to detect the presence of porcine. Universal TaqMan qPCR assay was found to amplify this commercial as positive amplification with the Cq value of 27.450.25 while there was no amplification occurred at both MPRE and Cyt b. Justification was made to this outcome. The amplified amplicon from the Universal assay was cloned to generate the sequence. No porcine DNA was traced from the sequence using the blast tool. This Halal authentication for the cosmetic cream on the other hand has become a great challenge to deal with as the fragmented DNA or too low amount of porcine DNA from the sample.